The Impact Of Current Ratio And Gross Profit Margin Towards Financial Distress In Technology Sector Companies Listed In Indonesia Stock Exchange For Period 2016-2020 - Ciptawan, Ciptawan; Frandjaja, Brian Owen (AGUSPATI Research Institute, 2022)
The growth of the Indonesian economy has increased rivalry among technological companies. Due to the fact that Indonesia's economy is still in its development, firms cannot be guaranteed to survive. Financial ratios can be used to foresee a company's bankruptcy, which has a huge influence on its investors; further analysis and study are required to forecast future financial distress. Thus, the purpose of this study is to ascertain the effect of the current ratio and gross profit margin on financial distress. This study employs a quantitative method based on secondary data. Between 2016 and 2020, the population is Technology Industry Companies Listed on the Indonesian Stock Exchange. A purposive sampling technique is use to determine 35 samples. The findings of this study indicate that Current Ratio does not have significant impact on business financial distress, similar to how Gross Profit Margin does not have significant impact on firm financial distress. Finally, both the current ratio and gross profit margin have a simultaneous impact but not significant on a firm's financial distress. Keywords : Current Ratio, Gross Profit Margin, Financial Distress